Investigation of the Potential Mechanisms Underlying Nuclear F-Actin Organization in Ovarian Cancer Cells by High-Throughput Screening in Combination With Deep Learning - Wu, Wei; Xing, Xiaoxia; Wang, Mingyang; Feng, Yinzhou; Wietek, Nina; Chong, Kay; El-Sahhar, Salma; Ahmed, Ahmed Ashour; Zang, Rongyu; Zheng, Yiyan (Frontiers in Cell and Developmental Biology, 2022)
Increasing evidence supports the notion that filamentous actin (F-actin) and globular actin exist in the nuclei of somatic cells, and are involved in chromatin remodeling, gene transcription regulation and DNA damage repair. However, the underlying mechanisms of how nuclear F-actin are polymerized in cells remain incompletely understood. Here, we identify potential kinase targets that participate in nuclear F-actin polymerization in ovarian cancer cells using small-molecule inhibitor library screening in combination with a deep learning approach. The analysis of the targets of the inhibitors used in this study suggest that the PI3K-AKT pathway are involved in regulating nuclear F-actin organization in ovarian cancer cells. Our work lays the foundation for uncovering the important roles of nuclear F-actin in the context of ovarian cancer, and for understanding how nuclear F-actin structures are organized.